2007
DOI: 10.1088/0957-4484/18/12/125304
|View full text |Cite
|
Sign up to set email alerts
|

Nanotextured super-hydrophobic transparent poly(methyl methacrylate) surfaces using high-density plasma processing

Abstract: We present an environmentally friendly, rapid, no-rinse and mass-production amenable plasma process for the fabrication of super-hydrophobic (SH) poly(methyl methacrylate) (PMMA) surfaces using only a one load/unload step in a low-pressure, high-density plasma reactor. First, oxygen plasma is applied to nanotexture the PMMA surface via etching processes leading to high aspect ratio (HAR) topography, with dual-roughness characteristics for short process durations, as evidenced by AFM analysis. The duration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 42 publications
8
108
0
3
Order By: Relevance
“…The surfaces are rendered hydrophobic -not superhydrophobic-by means of dry [24][25][26] or wet chemical processing [27]. Initially water droplets are sticky; sliding angle measurements are given hereafter.…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…The surfaces are rendered hydrophobic -not superhydrophobic-by means of dry [24][25][26] or wet chemical processing [27]. Initially water droplets are sticky; sliding angle measurements are given hereafter.…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…This observation is sound with effects reported in appropriate literature. Namely, many authors have shown that a treatment of organic materials with gaseous plasma leads to increased surface roughness [77,[81][82][83]. While the effect is not yet fully understood, a plausible explanation is selective interaction with amorphous and crystalline segments of cellulose materials.…”
Section: Plasma Treatment Of Cellulose Wound Dressingmentioning
confidence: 99%
“…A three-dimensional plasma micro-nanotextured cyclo-olefin-polymer surfaces has been used for biomolecules immobilization because of its environmentally stable superhydrophobic and superoleophobic properties. 10 Plasmas could also be used to deposit fluorocarbons on a cyclo-olefin polymer to enhance hydrophobicity 11 with good adhesion and effective surface protection reducing plastic deformation. A micro reactive ion-etching method has been used to prepare nanotextured films from PDMS for enhanced cancer cell isolation.…”
Section: Introductionmentioning
confidence: 99%